2010
DOI: 10.1071/sr10014
|View full text |Cite
|
Sign up to set email alerts
|

Effect of banded biochar on dryland wheat production and fertiliser use in south-western Australia: an agronomic and economic perspective

Abstract: Effects of banded biochar application on dryland wheat production and fertiliser use in 4 experiments in Western Australia and South Australia suggest that biochar has the potential to reduce fertiliser requirement while crop productivity is maintained, and biochar additions can increase crop yields at lower rates of fertiliser use. Banding was used to minimise wind erosion risk and place biochar close to crop roots. The biochars/metallurgical chars used in this study were made at relatively high temperatures … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
95
4
3

Year Published

2014
2014
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 210 publications
(120 citation statements)
references
References 26 publications
9
95
4
3
Order By: Relevance
“…Our result is also supported by [22]. [23] who reported that appliance of biochar improved the yields of crops due to better …”
Section: Grain Yield (Kg•ha −1 )supporting
confidence: 79%
“…Our result is also supported by [22]. [23] who reported that appliance of biochar improved the yields of crops due to better …”
Section: Grain Yield (Kg•ha −1 )supporting
confidence: 79%
“…As for plant growth responses, increases in foliar nutrient concentrations seen with S. saman and S. multiflora are both supported and refuted by the literature (Liang et al 2006;Blackwell et al 2010;Lehmann et al 2011). This present study indicated that although there was no clear increase in foliar N levels with the addition of compost, levels of foliar P and K were both found to have increased following this treatment.…”
Section: Plant Responses To Compost and Biochar Additionmentioning
confidence: 51%
“…While most biochar applications described so far consisted of homogenous spreading and ploughing over the whole field plot, conservative farming practices propose to apply soil amendments in a more concentrated fashion and close to the roots, e.g., in the hoe basins or rip lines where cultivation occurs [33][34][35]. Blackwell et al [36] tested banded biochar application on dry land wheat production and concluded that the banding application of biochar at low application rates of 1 t·ha…”
Section: Introductionmentioning
confidence: 99%